Livestock, Climate, and Security: A Policy Coherence and Awareness Analysis - Schapendonk, Frans; Scartozzi, Cesare M.; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2022)
The African livestock sector is expected to grow exponentially in importance both economically and nutritionally in the coming decades. In the context of Kenya specifically, human population, per-capita income, and urbanisation rates – key drivers for increased usage of animal-source food – are all expected to drastically increase in the coming decades. Yet despite the sector’s growing importance for Kenya and the African continent more broadly, there remain notable barriers to sustainable development within the context of livestock. One of the most important of these is the climate crisis and the impacts it will likely have on livestock production systems and value chains, the ecological contexts they exist within, and the communities reliant upon them.